From theory to practice: Land use planning in the Gwich'in Settlement Area - Greening, Hillaire; Gonzales, Neida (Canadian Institute of Planners, 1999)
Land use planning in the Gwich'in Settlement Area is based on a co-management framework in which a variety of stakeholders work together in a formal relationship. Comanagement represents a shift in resource management, from a "top-down" government-led process to one that is inclusive and involves a variety of stakeholders in decision-making processes. The Gwich'in Land Use Planning Board uses a community-based planning approach to develop its land use plans. The local communities in the Gwich'in Settlement Area play a special role in the process, as the Planning Board is mandated to deal with community issues within the context of land claims and comanagement. Planners play a unique role as facilitators. They are required to find innovative and flexible methods of achieving goals. L'aménagement du territoire dans la zone d'établissement de Gwich'in s'inscrit dans le cadre d'une cogestion où diverses parties prenantes collaborent de manière officielle. En matière de gestion des ressources, le principe de la cogestion marque le passage d'un processus pyramidal dirigé par le gouvernement à une politique de participation et de prise de décisions de la part des parties intéressées. C'est en collaborant avec ces dernières que le Conseil de l'aménagement du territoire de Gwich'in peut servir davantage les intérêts de la communauté. Les collectivités locales dans la zone d'établissement de Gwich'in jouent un rôle particulier dans ce processus alors que le Conseil a pour mandat le règlement des problèmes d'ordre communautaire dans les revendications territoriales et l'établissement des bases de la cogestion. Le rôle des urbanistes est capital dans la mesure où ils facilitent la collaboration dans le cadre de cette cogestion formelle. Dans cette optique, on attend d'eux qu'ils fassent preuve de souplesse et d'originalité pour atteindre les objectifs. https://viurrspace.ca/bitstream/handle/10613/6511/Greening.pdf?sequence=3 Abstract in English and French; text in English.